2020
DOI: 10.1007/s00239-020-09946-0
|View full text |Cite
|
Sign up to set email alerts
|

Recombination Between High-Risk Human Papillomaviruses and Non-Human Primate Papillomaviruses: Evidence of Ancient Host Switching Among Alphapapillomaviruses

Abstract: We use all the currently known 405 Papillomavirus (PV) sequences, 343 curated PV sequences from both humans and animals from the PAVE data base, to analyse the recombination dynamics of these viruses at the whole genome levels. After showing some evidence of human and non-human primate PV recombination, we report a comprehensive recombination analysis of all currently known 82 Alphapapillomaviruses (Alpha-PVs). We carried out an exploratory study and found novel recombination events between High-Risk HPV Types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…PVs exhibit a slow but astonishing evolutionary success, and traditional assumptions about the mechanisms of PV evolution include that they have very low mutation rates, co-diverge with their hosts and are host-specific [3,[39][40][41]. However, various alternative mechanisms that drive PV evolution have recently been proposed, such as cross-species transmission, recombination and incongruence in the phylogenetic trees of viruses and their hosts [3,40,[42][43][44]. The general conclusions about PV evolution may still be unclear and speculative, as knowledge about nonhuman PV diversity is particularly unbalanced and limited [3,42,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PVs exhibit a slow but astonishing evolutionary success, and traditional assumptions about the mechanisms of PV evolution include that they have very low mutation rates, co-diverge with their hosts and are host-specific [3,[39][40][41]. However, various alternative mechanisms that drive PV evolution have recently been proposed, such as cross-species transmission, recombination and incongruence in the phylogenetic trees of viruses and their hosts [3,40,[42][43][44]. The general conclusions about PV evolution may still be unclear and speculative, as knowledge about nonhuman PV diversity is particularly unbalanced and limited [3,42,45].…”
Section: Discussionmentioning
confidence: 99%
“…The bovine BPV-1 and BPV-2 types that infect cattle provide an example of cross-species transmission, not only between closely related hosts but also between more distantly related species, as they also infect buffaloes, bison, yaks, giraffes, tapirs, sable antelope, horses, donkeys and red deer [11,12,14,46]. The assumption that virus-host co-divergence alone was the driving force for current PV diversity has also been opposed by several studies describing distantly related PVs infecting the same host species, leading to incongruence in the phylogenetic trees of the viruses and their hosts [3,[42][43][44]. In this study, very low variability between the CcaPV1-type genomes (99.95% identity at the complete genome level compared to the sequences deposited in GenBank) and the CePV1v-type variant genomes (99.96-99.99% identity at the complete genome level compared to the sequences deposited in GenBank) was observed, with five out of six CcaPV1 genomes being 100% identical.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to focus on the cultivation of students' listening and speaking skills in English teaching, to enhance students' ability to use the language and to use it flexibly in practice [8][9]. And in this process, we realize the change of teaching philosophy and teaching methods, so that students can break through the shackles of exam-oriented education in learning and become innovative and practical comprehensive talents, and then better realize English communication [10][11]. When students learn English, they also tend to transition from listening to reading and writing, but in the actual English teaching, the proportion of listening teaching content is much lower compared with vocabulary, grammar and reading.…”
Section: Introductionmentioning
confidence: 99%
“…Although DNA viruses are considered to recombine with significantly lower frequency than RNA viruses [24], nevertheless, there have been reports of homologous [25,26] and even non-homologous [27] recombination among distant lineages of animal papillomaviruses. Recombination has also been reported among members of alpha-HPVs [28][29][30] and even among HPV16 lineages [31,32]. These reports indicated that HPV16 inter-lineage recombination may occur during infection, however the prevalence of recombinant HPV16 strains or the impact of these recombination events on viral pathogenicity remains unclear.…”
Section: Introductionmentioning
confidence: 99%